Revisiting the Distinctive Nature of Translation Studies and its Relation with Linguistics and Literary Studies - Ajmal, Muhammad; Suhail, Sarwat; Rafique, Hina (Annals of Human and Social Sciences, 2022)
The main objective of this article is to revisit the distinctive nature of Translation Studies (TS) and its relation with Linguistics and Literary Studies. By utilizing qualitative and content analysis approach, Translation Studies has been viewed as a multidisciplinary field that draws on a variety of disciplines such as linguistics, literary studies, cultural studies, and philosophy. The researchers argue that TS should not be reduced to a mere application of linguistic and literary theories, but rather recognized as a discipline with its own unique concerns, theories, and methodologies. The researchers also discuss the relationship between TS and Linguistics and Literary Studies, highlighting the complementary nature of these fields and the potential for interdisciplinary collaboration. The article recommends for a call for renewed recognition of the distinctive nature of TS and its important role in understanding the complex processes of communication and cultural exchange in a globalized world.